Groundwater use in North Africa as a cautionary tale for climate change adaptation. Issue 6 (18th August 2017) - Kuper, Marcel; Amichi, Hichem; Mayaux, Pierre-Louis
ABSTRACT: The recent history of groundwater use in North Africa provides a cautionary tale for climate change adaptation. Even though the short-term threats of groundwater overexploitation are clear, and territorially bounded, and involve comparatively few players, in recent decades, agricultural intensification has consistently increased pressure on the available resources. Groundwater has been governed through a dynamic interplay between formal rules and informal practices that focused more on maintaining fragile socio-political compromises than on ensuring environmental sustainability. If it is to be effective, climate change adaptation will need to muster the sort of political legitimacy that sustainable groundwater management is currently lacking.